Anti-Melanogenic Effect of Cannabis sativa Stem Extracts Fermented with Weissella paramesenteroides - Kim, Taehyun; Kim, Jinwoo; Min, Huitae; Park Jisu; 김태정; 김근형; 박병준; 김정국; Park, Young Tae; 김진철; Ham, Jung yeob (한국미생물·생명공학회, 2023)
Cannabis sativa (CS) has been in the spotlight not only for its medical uses but also as a raw material for cosmetics. As fermented cosmetics are known to have various health benefits, they have been extensively researched. Here, we investigated the characteristics of CS stems fermented using various gut microbes. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide assay and melanin content analysis revealed that melan-a cells containing CS stems fermented with Weissella paramesenteroides (CSWP) showed considerably reduced melanin content. Additionally, CSWP downregulated the expression of several melanogenesis factors, tyrosinase-related protein-1, and tyrosinase-related protein-2. This study suggests that the anti-melanogenic effect of CSWP could provide a new basis for the development of skin-lightening agents.